The Effect of Problem-Based Learning Model Using Contextual Teaching Learning Approach Viewed from Logical Mathematical Intelligence - Vivi Astuti Nurlaily; Heribertus Soegiyanto; Budi Usodo (Journal of Education and Learning (EduLearn), 2018)
This research is aimed at determining 1) the difference of learning achievement using problem-based learning through contextual teaching learning and direct learning in Mathematics learning; 2) the difference of learning achievement among high, medium, and low logical Mathematical intelligence; and 3) the interaction between learning model and logical Mathematical intelligence on the students’ learning achievement in Mathematics. The research was designed using quasi-experimental study of 2x3 factorial design. The population of this research was the third-grade students of elementary school. The data of students’ learning achievement in Mathematics and their logical-Mathematical intelligence was obtained using test. The data were analyzed using two-way ANOVA. The results of the research show that 1) Problem-based learning model using contextual teaching approach makes the students obtain better learning achievement than direct learning model; 2) the students having high logical Mathematic intelligence get better learning achievement than those having medium and low logical Mathematic intelligence, the students having medium logical Mathematic intelligence gets better learning achievement than those having low logical Mathematic intelligence; 3) there is no interaction between learning model and logical Mathematic intelligence on the students’ learning achievement.